Robot-assisted therapy in stratified intervention: a randomized controlled trial on poststroke motor recovery - Liu, Yang; Cui, Lijun; Wang, Jixian; Xiao, Zihao; Chen, Zhi; Yan, Jin; Niu, Chuanxin M.; Xie, Qing (Frontiers in Neurology, 2024)
Objective To compare the effects of robot-assisted therapy with conventional therapy for accelerating stratified intervention in poststroke patients with upper limb dysfunction. Background For stroke survivors, recovery of upper extremity function remains a major challenge in rehabilitation. Literature has suggested that the rate of recovery may improve if treatments can be individualized to their clinical profiles. However, there still lack clinical evidence on how to create treatment tailored to individual patients. Robot-assisted Therapy (RT) provides a straightforward approach to adjustment of the assistance-resistance continuum for individual patients. In early Brunnstrom stages of recovery, patients benefit from assistance training, whereas in later stages the training is favored with resistance. Therefore, RT may enhance Conventional Therapy (CT) but the use of RT in stratified intervention has not been investigated. This study evaluated the possible benefit of adopting RT following a protocol of upper-limb training, which was stratified with the Brunnstrom stage of each individual. Methods This study was a single-blinded randomized controlled trial. A total of 53 patients with stroke were recruited and randomized into 2 groups (CT, n = 27, 3 dropped out and RT, n = 26, 2 dropped out). Both groups were trained once per day, 5 days per week for 4 weeks. The CT group received 30 min of conventional therapy; the RT group received 30 min of upper limb robot-assisted training. Patients were assessed at the beginning, week-2, and week-4 of the treatment. The outcome measures included the Fugl-Meyer Assessment Upper-Extremity (FMA-UE) and the Modified Barthel Index (MBI). Results Across the 4-week intervention, participants in the RT group recovered 1.979 points of FMA-UE per week, compared to 1.198 points per week in the CT group (t94 = 3.333, p < 0.01); the recovery rate was 0.781 points/week higher in the RT group than in the CT group. Moreover, the recovery of FMA-UE was faster in proximal joints (t94 = 3.199, p < 0.01), and for patients in Brunnstrom Stage III (t34 = 2.526, p < 0.05). The improvements in MBI were not significantly different between RT and CT. Conclusion Robot-assisted therapy showed initial evidence for the acceleration of post-stroke recovery of motor function in the upper limb. Initial observations suggested that patients in Brunnstrom recovery stage III might benefit the most from the stratified intervention assisted by robotics. Clinical trial registration https://www.chictr.org.cn/showproj.html?proj=61834, Identifier [ChiCTR2000039010]. Registered 13 March 2020.